2019
DOI: 10.1177/0022042619861273
|View full text |Cite
|
Sign up to set email alerts
|

Diversion and Alternatives to Arrest: A Qualitative Understanding of Police and Substance Users’ Perspective

Abstract: Diversion to treatment is not a new concept in the criminal justice system. Successful strategies require the participation of both law enforcement officers and individuals with a substance use disorder (SUD). This study relies on interviews and focus groups to explore the perceptions and attitudes of these two different populations about non-arrest programs. From the police perspective, the study found that the biggest barrier to using alternatives is the police culture, while championship by leadership and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…But whatever positive momentum has resulted from COVID-19, sustaining it is far from guaranteed. In many jurisdictions, both policies and practices of the criminal legal system have exhibited a stubborn resistance to reform ( Barberi & Taxman, 2019 ). These failures to adapt to a new reality have impeded pandemic response, while putting frontline staff at risk of infection.…”
Section: No Going Back: a Vision For 21st Century Drug Policymentioning
confidence: 99%
“…But whatever positive momentum has resulted from COVID-19, sustaining it is far from guaranteed. In many jurisdictions, both policies and practices of the criminal legal system have exhibited a stubborn resistance to reform ( Barberi & Taxman, 2019 ). These failures to adapt to a new reality have impeded pandemic response, while putting frontline staff at risk of infection.…”
Section: No Going Back: a Vision For 21st Century Drug Policymentioning
confidence: 99%
“…34,35 What also emerges from the limited insights into police officer attitudes is the importance of law enforcement leaders advocating for treatment alternative programs and the practical need of collaborations with community health agencies in order to have diversion be successful. 34 Over time, enrollment numbers will continue to rise as the number of law enforcement partnerships with healthcare programs increase, officers are trained and communities are educated, stigma decreases, reliable access to treatment improves, and success stories emerge. 30…”
Section: Limitations and Policy Implicationsmentioning
confidence: 99%
“… 33 Researchers examining perspectives on diversion programs found that a majority of police officers reported police culture as a barrier to adopting treatment options in lieu of arrest, and that clients of law enforcement diversion programs had positive attitudes about the program yet still held negative attitudes about the justice system and police overall. 34 In the current study, the officers are trying to balance a public health initiative that requires intimate conversations with law enforcement while simultaneously trying to avoid being invasive in these brief interactions. All referrals in this partnership are the choice of the individual and are completely voluntary (no mandating), which could result in a self-referral bias between those who agree and those who decline, despite the best objective efforts by officers to connect everyone to treatment.…”
Section: Limitations and Policy Implicationsmentioning
confidence: 99%
“…The first phase of this research was conducted to examine the effect of police culture on patrol officer attitudes, in particular towards the use of RJ. There is support for the notion that police culture can act as a barrier to policy implementation and changes within policing (Alarid & Montemayor, 2012;Gottschalk & Gudmundsen, 2008;Barberi & Taxman, 2019), and how entrenched police practices can lead to police officers dominating RJ exchanges (Hoyle & Rosenblatt, 2016). It is this type of nuanced relationship between these concepts that can be explored and explained further through qualitative analysis.…”
Section: Resultsmentioning
confidence: 98%
“…The dilemma officers face with either arresting or diverting is common when diversionary practices are introduced into policing, and officers are faced with more than just one option of crime control. Barberi and Taxman (2019) explain this barrier to diversionary programs as on one side officers wanting to help people, but on the other they need to solve the call for service, keep the community safe and use their time wisely. This appears to be a "problem of displacement" (Woods & Suzuki, 2016: 156), which is the degree that restorative justice has moved into the realm of informal or diversionary criminal justice programs at largely the shallow end of the criminal justice system in terms of lesser offences or youth offending.…”
Section: Government Of Manitoba Notes That Increasing the Use Of Restmentioning
confidence: 99%